2020
DOI: 10.21315/mjms2020.27.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Health of Pre-Dialysis Chronic Kidney Disease Patients in a Northeast Peninsular Malaysia Tertiary Hospital

Abstract: Introduction: Chronic kidney disease (CKD) is associated with periodontal disease due to its hyperinflammatory state. Limited studies have explored the prevalence of periodontal disease among CKD patients in Malaysia. Objective: To assess the periodontal status of pre-dialysis CKD patients in Hospital Universiti Sains Malaysia. Methods: A total of 46 pre-dialysis CKD patients who attended the nephrology clinic at Hospital Universiti Sains Malaysia were enrolled in this study. Periodontal examination was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 27 publications
5
21
1
1
Order By: Relevance
“…In contrast to our findings, Ibrahim et al [ 23 ] reported no correlation between PI in healthy and pre-dialytic CKD groups as the sample size was small and the focus was only on one group (i.e., pre-dialysis). Further, no difference in PI between end-stage renal disease (ESRD) patients and control was seen.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to our findings, Ibrahim et al [ 23 ] reported no correlation between PI in healthy and pre-dialytic CKD groups as the sample size was small and the focus was only on one group (i.e., pre-dialysis). Further, no difference in PI between end-stage renal disease (ESRD) patients and control was seen.…”
Section: Discussioncontrasting
confidence: 99%
“…Significantly higher plaque scores were noted among the CKD patients of the study compared with healthy controls, which has been reported by previous studies [ 3 , 9 , 22 ] The association of poor oral hygiene with CKD may be linked to the consumption of antidiuretic drugs, which may impair salivary flow, thus reducing lubrication in the oral cavity and further promoting plaque accumulation [ 23 ]. In addition, oral healthcare practice was insufficient, which may, in turn, worsen the oral hygiene of these patients [ 24 ].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Em concordânia com o que foi apresentado, Ibrahim (37) relaciona os achados de problemas periodontais em pacientes submetidos a tratamentos renais ao uso de drogas antidiuréticas que reduzem o fluxo salivar, de modo a impedir a correta lubrificação da cavidade oral, provocando o acúmulo de placa. Ademais, a falta de assistência e instrução em saúde bucal e a situação de vulnerabilidade dos pacientes também corroboram significativamente para o quadro.…”
Section: Doença Renal Crônicaunclassified